Sistem Konten Pembelajaran di Indonesia : Systematic Literature Review - Dhomas Hatta Fudholi; Insanur Hanifuddin; Sri Mulyati (Ultimatics : Jurnal Teknik Informatika, 2021)
Wikipedia is the largest web-based digital encyclopedia today that contains almost all knowledge in general. On Wikipedia many readers have difficulty finding accurate information about the topic they are looking for, as content on Wikipedia usually contains only an overview of the topic referenced from some existing references. This study aims to examine Wikipedia, other encyclopedias and other online media that contain specific topics with their target users. The study was conducted on literature related to Wikipedia, encyclopedias, education and children's interests, especially at the elementary school level. Literature search is done by including some of the main keywords in Google Scholar such as "Wikipedia", "encyclopedia", "elementary school curriculum", "educational content" and "learning media". Literature is also obtained through the official website of the Ministry of Education and Culture which contains elementary and junior high school education standards, educational assessment standards, and literacy and numeration learning modules at elementary level. The results of literature analysis include 4 classifications based on topics, namely evaluation of usage, content, online learning and media. Based on the results of the analysis found that there has not been much research on the digital encyclopedia for education.